Emotional Intelligence and Personality : Their Relationship in the Indian Context - Dhani, Priyam; Sharma, Tanu (Prabandhan: Indian Journal of Management, 2017)
Emotional intelligence (EI) has created a buzz in the academic and corporate world; it is the ability to comprehend and control emotions and use the same as a guide towards effective behavior. EI is very essential as it affects the conduct of an individual profoundly, which is an after-effect of personality. Hence, personality can explicitly be related to emotional intelligence. The purpose of this study is to examine the relationship between EI and the nine personality traits; empathy, ego - ideal, pessimism, introversion, neuroticism, need achievement, self- confidence, dogmatism, and dominance. The sample for this study included 685 managers from a number of organizations of the service sector in India (banking, education, health care, IT, and advertising). The data were collected with the help of self-report measures, that is, DKEIT which is used to measure EI and MPI used to measure personality traits. Correlation and regression analysis were performed to find the relationship between the dependent and independent variables. The results of correlation analysis showed a relationship between EI and six personality traits (empathy, ego-ideal, pessimism, introversion, neuroticism, and self confidence). The stepwise regression models provide support for the association between emotional intelligence and personality traits. No significant relationship was found between emotional intelligence and three personality traits, which are need - achievement, dogmatism, and dominance. The sample of the study was delimited to middle level management from five service sectors, which is not truly representative of all the employees in the organization, and the study can be expanded to the employees of the entire organization and other sectors. Practical and managerial implications of the study are discussed in the article. The present study contributes to a growing body of literature seeking to find the relationship between emotional intelligence and personality. This is one of the first studies where self-report measures DKEIT and MPI were used, which makes this study unique. Both of the tools are developed in India, which added value to the study.